Colombia, un estado social de derecho simbólico : tensiones legales y prácticas frente al porte y consumo de la dosis mínima y el libre desarrollo de la personalidad (2018)
"Colombia is a symbolic social law State because it recognizes jurisprudentially that the right to free development of the personality of the subjects that inhabit it can be exercised through the consumption and possession of narcotics, but limits the exercise of the same through its laws. That is why this article investigated the legal ambiguities present in the Colombian legal system, to understand how they condition the way in which subjects (police and consumers) face specific situations related to the materialization of the right to the free development of the personality through the consumption of narcotics." -- Tomado del Formato de Documento de Grado.